Pelatihan Penggunaan Sistem Monitoring Kolam Lele dan Alat Pakan Lele Otomatis Berbasis Internet of Things (IoT) pada Kelompok Tani Tnoposeo 1, Desa Oetalus - Nababan, Darsono; Sucipto, Willy; Getrudis Manek, Patricia; Grace Ludji, Dian; O L Rema, Yasinta (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
The current precision farming system is the right step in an effort to increase production or yield from the farm, one of which is the importance of a control system for feeding and measuring water quality in catfish farming. The farmer group in Oetalus village, northern TTU district is a farmer Nababan, et al. PkM Sistem Monitoring Kolam Lele Berbasis Internet of Things (IoT) pada Kelompok Tani Tnoposeo 1 Desa Oetalus Copyright © 2024 Nababan, et al. Published by Institute for Research and Community Service, Atma Jaya Catholic University of Indonesia. This articles is licensed under a Creative Common Attribution-NonCommercial-Share Alike 4.0 International License. 76 group that cultivates catfish traditionally, with a traditional farming system, various problems arise such as poor water quality, the presence of dead catfish due to catfish that have a cannibal system so that the production of farmers is less than optimal. In overcoming these problems, the PkM team provides a solution by developing an aquuture system with the support of the Internet of Things (IoT) for feeding and measuring water quality. The PkM method is carried out by means of socialization and direct training for making automatic feed and monitoring water quality. The location of the PkM implementation is about 7 Km with a total of 20 farmer groups. The catfish feed control system is carried out with the support of smartphones and telegram applications. From the evaluation of this activity, in general, farmer groups feel helped with a satisfaction level of 90% but there are still various obstacles related to network conditions and understanding of farmer groups related to IoT so that consistent assistance is needed to support future precision agriculture / livestock systems.